2006
DOI: 10.1007/s00442-006-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and within-population variation in the globeflower–globeflower fly interaction: the costs and benefits of rearing pollinators’ larvae

Abstract: Interspecific interactions can vary within and among populations and geographic locations, and this variation can influence the nature of the interaction (e.g. mutualistic vs. antagonistic) and its evolutionary stability. Globeflowers are exclusively pollinated by flies, whose larvae feed only on their seeds. Here we document geographic variability in costs and benefits in globeflowers in sustaining their pollinating flies throughout the range of this arctic-alpine European plant over several years. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 29 publications
2
20
2
Order By: Relevance
“…Substantial inter‐year differences (see Figs 3a, 3b and 4b) and much variation among populations are found in our own results, despite the populations being from similar geographical and altitudinal localities. Thus, differences in year, altitude and locality across populations might, possibly, confound the detection of such responses in the Despres et al. (2007) study.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial inter‐year differences (see Figs 3a, 3b and 4b) and much variation among populations are found in our own results, despite the populations being from similar geographical and altitudinal localities. Thus, differences in year, altitude and locality across populations might, possibly, confound the detection of such responses in the Despres et al. (2007) study.…”
Section: Discussionmentioning
confidence: 99%
“…large flowers had higher visitation rate), while the length of the flowering stem had no impact on Chiastocheta attraction (Ibanez et al 2010). Furthermore, a large scale survey of 38 natural populations in the French Alps and in the Arctic showed that large flowers hosted more larvae and ultimately dispersed more undamaged seeds than smaller flowers (Després et al 2007). Although there was no difference in fly fitness (larval installation success, larval size and fresh mass) of larvae inhabiting large and small flowers (Després and Cherif 2004).…”
Section: Discussionmentioning
confidence: 97%
“…plants that are likely to make use of the pollination service without rewarding pollinators with seeds. Large flowers are generally more attractive to egg-laying females (Després et al 2007), and among flowers of different sizes in natural populations, the ones found without developing larvae (actually very few) are always significantly smaller than average (Jaeger et al 2001;Després et al 2007). Small flower genotypes (if they existed) could disrupt the balance of this interaction if they were to obtain sufficient pollen without paying the cost of seed predation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations